Fixed Assets Management Strategies for Official Vehicles in Riau Islands Provincial Government - Salman Al Farisi; A. Faroby Falatehan; Dwi Rachmina (PT Mattawang Mediatama Solution, 2024)
The objectives of this research are: 1) to analyze and evaluate the management of official vehicle fixed assets in Riau Islands Provincial Government; 2) to examine the internal and external factors influencing the management of these assets; and 3) to develop strategies for improving the management of official vehicle fixed assets in Riau Islands Provincial Government. The selected respondents were the user goods managers or assistant goods managers in regional apparatuses responsible for carrying out the administrative functions of regional property management (BMD) at the goods management level. In addition, policymakers in the Inspectorate and the Regional Financial and Asset Management Agency (BPKAD) of Riau Islands Province were the respondents to formulate policy strategies. The gap analysis results were divided into planning, implementation, as well as supervision and control. The highest gap in planning was presented in the Regional Government Budget Proposal (RKMBD), the availability of regional property in the user environment, and the preparation of proposals for the disposal of regional property, with a gap score of 0,11-0,15. Furthermore, the highest gap in implementation is in the range of 0,59-1,63. The issues with the highest gap are shown in the variables of using official vehicles for non-official purposes, ownership of official vehicles that do not comply with regulations, and the administration of borrowing official vehicles. The supervision and control section variables show gaps in user monitoring with a gap score of 0,07. Identifying critical external and internal factors is the initial step in formulating alternative strategies to address the existing issues in the SWOT analysis input process. In the internal factor analysis, policies supporting the management of official vehicles by Riau Islands Provincial Government received the highest score. In contrast, the weakness factor, namely the lack of a sustainable official vehicle monitoring system, received the lowest score. According to the analysis, the external factor (opportunities) received the highest score, followed by the increased accessibility of vehicle monitoring technology and the sanctions imposed by BPKAD on regional apparatuses that fail to reconcile assets. The external factor (threats) received the highest score, followed by the low compliance of regional apparatuses with applicable regulations.